THE USE OF ULTRAVIOLET RADIATION IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS - Olimov Mukhsinbek Sotivoldievich (Proximus Journal Publishing, 2025)
In all levels of the existing sports education system in Uzbekistan, as well as in sports clubs and privately operated sports facilities, ensuring the disinfection of air and equipment surfaces through the use of ultraviolet radiation, creating a hygienic and healthy environment free from microbes and infections for participants with minimal labor input, preventing the spread of infectious diseases, and educating young people to comply with general and personal hygiene rules are among the most pressing issues of today. To address these challenges, the technology titled “The Use of Ultraviolet Radiation in the Field of Physical Education and Sports” has been developed.
Keywords: Ultraviolet radiation; Light waves; Biochemical